CUSTOMER SATISFACTION AND PROMOTION OF TOURISM: A STUDY OF MANIPUR STATE MUSEUM, IMPHAL - Thomas, Chithung Mary; Devi, Waikhom Nichinta; Devi, Kshetrimayum Nevia (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Museums are an important component of tourism and they attract a large number of visitors who are curious about the nature of societies and historical past. Museum Tourism(MT) creates value for society by promoting education, recreation and cross cultural understanding among people. Manipur, in the north-east of India has a long, rich and diversified history and with its strategic location is set to become the “gateway to the east” as per the “Act-East Policy” of the Government of India. It has become pertinent to know about the region and its heritage. The Manipur State Museum, Imphal plays a major role in the preservation as well as disseminating information about the heritage of Manipur to the world as well as the younger generations. The purpose of this paper is to study the museum experiences of visitors and their level of satisfaction which in turn may affect customer loyalty and socio-economic ends.